Conspiracy culture : post-Soviet paranoia and the Russian imagination - Livers, Keith A., 1963- (University of Toronto Press, 2020)
"Contemporary Russia stands apart as one of the most prolific generators of conspiracy theories and paranoid rhetoric. Conspiracy Culture traces the roots of the phenomenon within the sphere of culture and history, examining the long arc of Russian paranoia from the present moment back to earlier nineteenth-century sources, such as Dostoevsky's anti-nihilist novel Demons. Conspiracy Culture examines the use of conspiracy tropes by contemporary Russian authors and filmmakers including the postmodernist writer Viktor Pelevin, the conservative author and pundit Aleksandr Prokhanov, and the popular director Timur Bekmambetov. It also explores paranoia as an instrument within contemporary Russian political rhetoric, as well as in Russian pseudo-historical works. What stands out is the manner in which Russian popular paranoia is utilized to express broadly shared fears not only of a long-standing anti-Russian conspiracy undertaken by the West, but also about the destruction of the country's cultural and spiritual capital within this imagined "Russophobic" plot."-- Provided by publisher.
Keywords: Russian fiction -- 20th century -- History and criticism.; Conspiracies in literature.; Paranoia in literature.; Conspiracies in popular culture -- Russia (Federation) -- History -- 20th century.; Paranoia in popular culture -- Russia (Federation) -- History -- 20th century.; Conspiracies in popular culture -- History -- 20th century.; Roman russe -- 20e siècle -- Histoire et critique.; Conspiration dans la littérature.; Paranoïa dans la littérature.; Conspiration dans la culture populaire -- Histoire -- 20e siècle.; Paranoïa dans la culture populaire -- Russie -- Histoire -- 20e siècle.; LITERARY CRITICISM / Russian & Former Soviet Union; Conspiracies in literature; Conspiracies in popular culture; Paranoia in literature; Paranoia in popular culture; Russian fiction; Russia (Federation); 1900-1999; Literary criticism; Criticism, interpretation, etc.; History; Literary criticism.; Critiques littéraires.